Influence of Particle Size and Chemical Activation on Rice Husk Biochar as Slow Release Fertilizer - Natasha Amelia Rigitha Akhwan; Avido Yuliestyan (Eksergi, 2020)
Nitrogen, Phosphate, and Potassium are important nutritional elements contained in the fertilizers for plants but their presence in the soil could be easily wash out by rain water. Biochar, originated from rice husks with a high absorbance ability, might be able to be used to inhibit the release of those nutrients. This research aims to investigate the influence of biochar size and the HCl chemical activation. Biochar, which has been pyrolyzed, was ground and sieved to obtain powder with the size average equivalent to 0.2735 mm; 0.4485 mm; 0.725mm; and 0.925 mm. The optimized biochar size were opted for later being activated using HCl with a concentration of 3%; 9%; and 15%. The leaching process of fertilizer, aiming to imitate the rain water washing, was performed by pouring water on a daily basis on a sand column with the presence of biochar saturated with colorized fertilizer. The obtained solution were then characterized using Spectrophotometer. The results show that the estimated release time for the case with the absence of biochar is 36 days, in contrast to 55 days for the case with the presence of biochar.